Start-up strategy of a thermophilic upflow anaerobic filter for treating palm oil mill effluent - Mustapha, S.; Ashhuby, B.; Rashid, M.; Azni, I. (Elsevier, 2003)
A thermophilic upflow anaerobic filter treating palm oil mill effluent was started up in a dm3 laboratory-scale reactor. The reactor was operated continuously at a thermophilic temperature 55°C for over 10 weeks with increased loadings of chemical oxygen demand (COD) of 0.1-0.5 kg COD m-3 day-1. The start-up strategy was accomplished over sequential increase of temperature of 0.5-1°C per day in which the mesophilic bacterial seed was gradually acclimatized to the thermophilic conditions. At these conditions, the reactor showed satisfactory results in organic removal efficiency (up to 97 and 94% for biological oxygen demand (BOD) and COD, respectively) and biogas production rates of 26.8-116.1 m-3 day-1 for organic loading rates varied from an initial value of 5.8 to 10.9 kg COD m-3 day-1. The thermophilic anaerobic filter was stable in terms of acidity and alkalinity. In this study, the start-up process of the thermophilic reactor was accomplished in a relatively short time and was stable under mesophilic conditions.